IDENTIFICATION OF OIL SLUDGE BAGS USING GEOMAGNETIC METHODS IN THE FIELD â€œXâ€ - Irjan, Irjan; Suhartono, Suhartono; Dwi Nur Amalina, Tiara Arum (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
Geophysical research using the geomagnetic method has been carried out in Sekarkurung village, Kebomas district, Gresik district using a Proton Procession Magnetometer (PPM). Geomagnetic data acquisition that has been carried out with an area of 700 x 400 meters has obtained 122 measurement points with a distance between rings of 30 meters. Based on the interpretation of local magnetic field anomaly values that vary from -22 nT to 12 nT. Based on the interpretation of the 2D subsurface modeling, there are 4 types of bodies or layers. The types of layers are: topsoil with a susceptibility value of 0.000020 cgs emu, reef limestone with a susceptibility value of 0.000005 cgs emu, limestone-chalt with a susceptibility value of 0.000026 cgs emu, and limestone with a susceptibility value of 0.000025 cgs emu and oil sludge pouch located at a depth of Â± 50 meters.Â